IMPROVEMENT OF OIL PAN BY USING VALUE ENGINEERING METHODOLOGY - K. Shanmugasundaram, Dhinakaran, S. Ezhilan (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
Valueengineeringisaproventoolforreducingcostsandincreasingthevalueoftheproducts.Thishasadirectbearingonimp rovedcompetitivepositioninthemarketplaceandincreasedprofitmargins.Thisprojectdescribestheimplementationofth istoolforanoilpandesigninICengine.ValueengineeringfortheOilpanaimsinreducingthecomplicatedmanufacturingby virtueoftheprocessandalsobyeffectiveutilizationofrawmaterial,whichdirectly resultsinreductionofmaterial &processcost.Thesimplifiedmanufacturingprocesswilleffectivelyimprovetheproductionratebyreducingthetimetake ntomanufacturetheproduct.Tofindthebest possible alternative from the choices we have incorporated a tool named as Decision Matrix. Decision Matrix gives the mostappropriate result and is even easy to use. The selected alternative method is modeled with Pro Engineer tool and is simulated inanalysistoollikeNASTRANtojustifytheachievedvibrationproperties.